Recommendations for the development of a tool for supporting early design decisions for the energy performance of office buildings in hot climates - Pedrini, Aldomar (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper introduces a method to estimate the influence of architectural design decisions on the building energy performance, during the early stages of the design. The study assumes that early design decisions are the most important and therefore suggests a method of assessment that is non-specific to the whole building geometry although may represent multiple forms and layouts. The tool is based on a graphic interface that is linked to a database, which as initially created to represent the office buildings of Brisbane Australia (warm humid summer and mild winter). The database consists of results of total and end-use electrical energy consumption of approximately 38 000 combinations of 11 variables: geographic orientation, room depth, ceiling height, window-wall ratio, vertical shading angle, horizontal shading angle, glass type, wall construction, day lighting and blinds control, ventilation type and efficiency of building services. The graphic interface allows the qualitative and quantitative study of combined effect of variables and the estimate of the design’s performance to be carried out. Due to the instantaneous access to the data-base by the interface, the consultation takes only a few seconds.